The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.3748/wjg.v13.i34.4610
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the role of gastric mucosa at the secretion of soluble triggering receptor expressed on myeloid cells (strem-1) in peptic ulcer disease

Abstract: sTREM-1 secreted by the gastric mucosa is an independent mechanism connected to the pathogenesis of peptic ulcer. sTREM-1 was released at the presence of H pylori from the inflamed gastric mucosa in the field of gastric ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Former results of our group revealed that the inflamed gastric mucosa was potent for the release of soluble triggering receptor expressed on myeloid cells (sTREM‐1) in peptic ulcer disease. Proinflammatory cytokines such as tumour necrosis factor‐α were released from the inflamed gastric mucosa independently from the inflammatory status [7]. Other authors have stated that cell loss and apoptosis of gastric mucous cells was enhanced by H. pylori LPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Former results of our group revealed that the inflamed gastric mucosa was potent for the release of soluble triggering receptor expressed on myeloid cells (sTREM‐1) in peptic ulcer disease. Proinflammatory cytokines such as tumour necrosis factor‐α were released from the inflamed gastric mucosa independently from the inflammatory status [7]. Other authors have stated that cell loss and apoptosis of gastric mucous cells was enhanced by H. pylori LPS.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 111 patients were enrolled; 47 patients with duodenal ulcer, 33 with gastric ulcer and 31 with chronic gastritis without peptic ulcer disease. Clinical and endoscopic data for 72 of these patients have already been published [7].…”
Section: Methodsmentioning
confidence: 99%
“…The explanation of the presented findings probably relies on former findings that sTREM-1 is an independent factor for the pathogenesis of peptic ulcer disease [3][4][5]. Its presence in gastric juice is related to the degree of infiltration of the gastric mucosa by inflammatory cells [3].…”
Section: Discussionmentioning
confidence: 70%
“…Its soluble counterpart, namely sTREM-1, is detected in the gastric juice of patients with gastric and duodenal ulcer and in the supernatants of cultures of the inflamed gastric mucosa in the field of a peptic ulcerative process [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Peptic ulcer disease could potentially elevate sTREM-1 levels. 37,38 Finally, but not least, the non-septic ARDS group in our study was defined by a retrospective review, which could have compromised our conclusion about the diagnostic value of sTREM-1 for sepsis, because of possible occult infections in the group that could not be ruled out. Clinically, precise prospective identification of non-septic ARDS is very difficult, because sepsis is always considered to be the causative differential diagnosis that is lethal if no adequate treatment is taken.…”
Section: Discussionmentioning
confidence: 97%